"I definitely think it's a feasible and worthwhile option": perspectives of speech-language pathologists providing online aphasia group therapy. Issue 9 (2nd September 2018) - Pitt, Rachelle; Hill, Anne J.; Theodoros, Deborah; Russell, Trevor
ABSTRACT: Background : Speech-language pathologists (SLPs) have begun to incorporate telepractice methods into clinical service delivery and online intervention for aphasia is recognised as an appropriate alternative to face-to-face services. However, little is known about the SLP experience of telepractice with no known study exploring the provision of aphasia group therapy online. The purpose of this study was to describe the experience of SLPs who provided the online aphasia group therapy, Telerehabilitation Group Aphasia Intervention and Networking (TeleGAIN), to people with aphasia (PWA) and their perceptions regarding the outcomes of intervention and feasibility of implementation into clinical practice. Aims: The aim of this study was to describe the experience of SLPs who provide TeleGAIN to people with aphasia including the perceived outcomes of the intervention and treatment procedures. Methods & Procedures : Three SLPs with experience in aphasia rehabilitation delivered at least one 12 week block of TeleGAIN – an aphasia group intervention purposefully developed for delivery via telepractice. Prior to TeleGAIN, SLPs were trained in using the technology required and the goals, activities, and constructs of TeleGAIN. The goals of TeleGAIN for PWA were to 1) create opportunities for communicative success, 2) share personal life history, and 3) provide support for living successfully with aphasia through networking with others. The SLPs provided this intervention to 21 PWA across six groups. Following completion of all treatment blocks, each SLP participated in a semi-structured interview exploring their perceptions of TeleGAIN and the potential for implementation. Interviews were analysed using qualitative content analysis and key categories were identified. Outcomes & Results : SLPs enjoyed providing the online aphasia group therapy TeleGAIN, and considered the intervention to be feasible and worthwhile. SLPs developed a range of strategies to manage the barriers to implementing the online group successfully and promoted those factors that facilitated more efficient and effective group sessions. In addition, benefits for individuals with aphasia, SLPs and SLP services were recognised despite challenges with technology and group dynamics experienced during TeleGAIN. Conclusions : The results from this study suggested that although SLPs may take time to improve their skills and confidence in telepractice, they were successfully able to provide online group aphasia therapy to PWA. The experience of the SLPs in this study suggested that commonly cited barriers to telepractice such as rapport building and technology issues were able to be overcome. SLPs perceived that TeleGAIN offered PWA many communication and psychosocial benefits and may improve SLP service provision. Findings support investigation of the implementation of TeleGAIN into clinical services.